IMPLEMENTATION OF SCIENTIFIC INTEGRATION CONCEPT MONITORING AND EVALUATION ON THE PESANTREN LEARNING CURRICULUM - Reni Nuraeni; Irawan Irawan (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
This study aims to determine the results of monitoring and evaluation of the implementation of curriculum integration carried out by an Islamic educational institution in Islamic boarding schools. The research was conducted at the Baitul Fikri Arcamanik Modern Islamic Boarding School in Bandung. The study uses a qualitative approach with the CIPO evaluation technique developed through observation and data collection with documentary data and structured interviews with rating-scale techniques. The results showed that the percentage value of the application of the concept of integration was in line with the results obtained with students' summative evaluation value data. The data on the application of the lowest integration concept is in Mathematics with a percentage of 55%, and the average summative value of students is 73, while the highest data on the application of the concept of integration is in PJOK subjects with a percentage of 77% and the average summative score of 81 students.